EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DALAM MENINGKATKAN PEMBANGUNAN FISIK DESA KARANG SARI KECAMATAN GUNUNG MALIGAS KABUPATEN SIMALUNGUN - Prihana, Noni; Siahaan, Yansen; Inrawan, Ady; Nainggolan, Christine Dewi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
AbstractThe objectives of this research are: 1. To find out the general description of the Village Fund Allocation management in the physical development of Karang Sari Village, Gunung Maligas District, Simalungun Regency. 2. To determine the effectiveness of the management of Village Fund Allocation in the physical development of Karang Sari Village, Gunung Maligas District, Simalungun Regency.This research uses field research and library research. Data collection in this research were questionnaires and documentation. Respondents in this research were several Village Consultative Bodies and village communities who understood the allocation of village funds in Karang Sari Village, Gunung Maligas District, Simalungun Regency. The analysis technique used is qualitative descriptive analysis and inductive analysis.The results of this research can be concluded that the physical development of Karang Sari Village, Gunung Maligas District, Simalungun District has been said to be effective. The physical development of Karang Sari Village has been carried out based on mutual agreement and deliberation. As well, Management of village fund allocation has been based on the principles of planning, implementation and supervision.The suggestion of the results of this research that the Karang Sari Village Government needs to develop some future development and socialize the allocation of village funds to all levels of society in Karang Sari Village, Gunung Maligas District, Simalungun Regency